Aplicación del proceso de atención de enfermería en RN con afecciones materna (clamidia) en el Hospital Universitario de Guayaquil. - Crespo Ruales, Manuel Ignacio (2020)
Maternal health is understood in the gestation period, in which all the physiological, psychological and welfare aspects of women are governed from conception, pregnancy, childbirth and postpartum, however, there are complications that harm both the mother and to the fetus and / or embryo, called maternal conditions that include multiple health problems that prevent this process from taking place in the best health conditions. Among the maternal conditions that are triggered in pregnancy we have sexually transmitted infections, such as chlamydia which is the most common, causing the newborn to conjunctivitis and pneumonia within the first 3 months of life. This clinical case was applied in the university hospital of Guayaquil, to publicize the fundamental bases of nursing diagnoses, being a necessary method that helps in the speedy recovery of the patient, as long as they help to meet the needs of the patient and their family members.